2018
DOI: 10.1007/s11418-018-1206-x
|View full text |Cite
|
Sign up to set email alerts
|

Appetite-enhancing effects of vanilla flavours such as vanillin

Abstract: Vanilla flavour is familiar to consumers through foods, cosmetics, household products and some medicines. Vanilla flavouring agents typically contain vanillin or its analogue ethyl vanillin. Our previous study revealed that the inhalation of eugenol, which contains a vanillyl group, has an appetite-enhancing effect, and the inhalation of aroma compounds containing the vanillyl group or its analogues led to increased food intake in mice. Here, we found that vanillin, ethyl vanillin and eugenol showed appetite-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 13 publications
0
28
1
Order By: Relevance
“…Previous studies reported that CP can induce gastrointestinal toxicity, [ 33 ] but vanillin can abolish the CP‐induced gastrointestinal toxicity and can enhance appetite. [ 34 ] Putting together, these effects might therefore explain the results of body weight gain seen in our study.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies reported that CP can induce gastrointestinal toxicity, [ 33 ] but vanillin can abolish the CP‐induced gastrointestinal toxicity and can enhance appetite. [ 34 ] Putting together, these effects might therefore explain the results of body weight gain seen in our study.…”
Section: Discussionmentioning
confidence: 55%
“…Vanillin exists naturally in various plants and can be produced by microbes from cinnamic acids ( Liao et al, 2013 ). Although vanillin is often used as a flavor compound in the food industry, experiments demonstrate that it can also enhance appetite ( Ogawa et al, 2018 ) and alleviate inflammation ( Cheng et al, 2017 ) and anxiety ( Wang et al, 2017 ). The hypoxia state of the large intestine is crucial in maintaining optimal health in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Vanillin has shown to have anticancer activity and to regulate inflammatory response and oxidative stress (6,7), and to be a powerful antimicrobial (8), also suitable to innovative application as in arthroplasty implants (9). Recently vanillin has proven to have appetite-enhancing effect (10) and to improve the gut microbiota composition on mice (11).…”
Section: Introductionmentioning
confidence: 99%